Increasing Teacher Performance Through Strengthening Transformational Leadership, Personality, and Work Motivation - Mokodompit, Rosnany; Setyaningsih, Sri; Suhendra (The Islamic Education and Multiculturalism Foundation, 2024)
This research aims to increase teacher performance and analyze the influence of transformational leadership variables, personality, and work motivation on the performance of private kindergarten teachers accredited